A Morning Coffee in Melbourne: Discussing the Contentious Spaces of Media Practice Research. Issue 1 (2nd January 2018) - Batty, Craig; Berkeley, Leo; Glisovic, Smiljana
Abstract: This is a conversation that took place between three practitioner-academics one morning in Melbourne. All three work and practice in the field of the moving image: from screen production to audiovisual installation to screenwriting. Our conversation is underpinned by previous research we have undertaken in this field, namely the launching of a moving image journal, Sightlines, and a companion journal article on the process of setting it up, which focussed on the issues presented when trying to establish peer review protocols and guidelines for moving image works.